A giant love story - Guðrún Helgadóttir 1935-2022 (Vaka-Helgafell, 2015)
When the dim-witted giantess Flumbra falls in love, her escapades upset all Iceland
Keywords: Giants / Juvenile fiction; Iceland / Juvenile fiction; Giants; Iceland; Fiction; Juvenile works; Bilderbuch